Management of the Hatred of Schooling by Public Secondary School Pupils - Solomon Modiba, Ngwako (International Journal of Criminology and Sociology, 2022)
This paper evaluates the cause of enmity and animosity displayed by pupils to their teachers through their hatred of schooling in myriad public educational institutions in South Africa. The paper was motivated by diverse discourses about pupil-animosity, most of which were based on the perspective of parents as members of the society. This paper is conceptual and empirical within the qualitative research paradigm. The question guiding this paper is: to what extent is the suppression of learner-desires and choices contribute to the snubbing of schooling? Narrative enquiry and interviewing techniques were used to collect data. Out of the population of 14 secondary schools in one of the circuits in Capricorn district in Limpopo Province, 6 were conveniently sampled. In each of the 6 sampled secondary schools, only Deputy Chairpersons of the School Governing Bodies became research participants. Findings revealed that hatred of schooling could be ascribed to pupils viewing schooling as an inconvenience. Secondly, failing to teach according to learners’ preferred teaching strategies. Thirdly, content delivery to pupils being alien. Fourthly, schooling that obstructs learner-hedonism. Fifthly, schooling that is naturally highly regimented. Lastly, schooling that suppresses learner-voice. The researcher recommends for schooling to close the generational gap between pupils and teachers. Furthermore, future schooling has to be conducted through virtual classrooms other than the tiresome face to face contact.